A minimum area piston for compression ignition engines - Leach, F; Davy, M; Ayyapureddi, S; Pierson, S; San Primitivo Rodriguez, J; Sammut, G (American Society of Mechanical Engineers, 2024)
Conventional compression ignition (diesel) engine combustion system, employ pistons with omega shaped bowls (or a very similar shape) combined with a swirl-based bulk air motion to ensure good fuel-air mixing. However, such bowls have a relatively large surface area:volume ratio, leading to significant heat loss, and are complex to design and manufacture. Recent advances in fuel injection technology, allowing higher injection pressures and multiple injection events and digital rate shaping, along with variable intake valve technology mean that achieving sufficient fuel-air mixing may now not require an omega shaped bowl. This work, then, introduces a new piston design for compression ignition engines that minimises the surface area:volume ratio, enabling less heat loss through the piston, higher durability, and a lighter and easier to produce piston. This novel piston design is evaluated against a conventional (omega) bowl piston (maintaining compression ratio and other parameters) at a variety of part and full load conditions in a single cylinder research engine. Emissions, fuel consumption, and combustion parameters are measured and presented alongside an energy balance. The results show that, depending on the load conditions, a 1.5–4% decrease in fuel consumption is noted alongside, at some load conditions, an increase in exhaust temperature (providing extra enthalpy for a turbocharger). The energy balance showed less energy lost to the oil with more energy in the exhaust.